Business intelligence and analytics systems for decision support - Sharda, Ramesh; Dalen, Dursun; Turban, Efraim (Always learning, 2014)
Decision Support and Business Intelligence Systems provides the only comprehensive, up-to-date guide to today's revolutionary management support system technologies, and showcases how they can be used for better decision-making.